Granular activated carbon‐based treatment and mobility of per‐ and polyfluoroalkyl substances in potable reuse for aquifer recharge. Issue 5 (24th September 2021) - Gonzalez, Dana; Thompson, Kyle; Quiñones, Oscar; Dickenson, Eric; Bott, Charles
Abstract: Hampton Roads Sanitation District recently initiated an indirect potable reuse project to recharge the Potomac Aquifer in southeastern Virginia, USA. Source control and granular activated carbon (GAC) treatment are employed to minimize per‐ and polyfluoroalkyl substances (PFAS) content in this water. Final purified water maintained low long‐chain perfluoroalkyl acids (PFAAs; <8 ppt sum of PFOA, PFNA, PFDA, PFHxS, PFOS) and moderately low short‐chain PFAAs (<118 ppt of sum PFBA, PFPeA, PFHxA, PFHpA, PFBS). High mobility of low concentrations of five PFAS (PFBS, PFPeA, PFHxA, PFHpA, PFOA) in the Potomac Aquifer was observed. Despite low concentrations relative to current guidelines, PFAS breakthrough and mobility support strict source control and the use of surrogates like total organic carbon to guide GAC operation at the installation. Article Impact Statement: Source control and granular activated carbon operation targeting 4 mg/L total organic carbon in effluent maintained low per‐ and polyfluoroalkyl substances concentrations in indirect potable reuse water.